A Critical Study on Madelung’s View towards the Discrepancy between Imam Hassan and Imam Ali PBUT - Mohammad Reza Barani; Zeinab Mirzaee Mehrabadi (تاریخ اسلام)
Wilfred Madelung, born in 1930 A.C, is considered as one of the western researcher of Islam with merely a fair approach along with a scientific motive regarding the study on the history of Islam. In his writings pertaining to the history of Imam Hassan’s life, he has investigated the issues like Imam’s marriages and divorces, his making peace as well as the elements of peace contract. Moreover, he has tried to answer the stated skepticism of other western researchers of Islam in relation to that holiness. However, he has stated some issues leading to the source of skepticisms related to Imam PBUH. The issues like the disagreement of that holiness with the objectives of Imam Ali PBUH, his lack of tendency towards taking charge of caliphate and his approving the way of ottoman’s governorship as well. This writing critically investigates these skepticisms and responds them on the basis of the historical and narrative Shiite and Sunnite sources